Best Arm Identification with Biased Contexts - Cheshire, James; Clémençon, Stephan (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
We study active mitigation of selection bias in statistical learning. That is sequential maximization over a set A of the expectation of a reward function R(a,X) w.r.t. a r.v. X drawn from a target distribution PT possibly different from the (supposedly dominating) source distribution PS under which rewards are observed. The importance function dPT/dPS (x) with which the sequentially observed biased rewards should be ideally weighted being unknown in practice, auxiliary information is assumed to be available in the form of known moments of the target distribution PT for debiasing purposes. In the batch setting, this problem has already been studied and can be solved under certain conditions in two successive steps: 1) identify a weight function so as to approximate the moments 2) maximize the resulting (empirical version of the) weighted reward. In the active setting, if the problem boils down to identifying the best arm in a stochastic multi armed bandit (MAB) model, the presence of selection bias strongly affects the complexity of the sequential optimization problem and requires the development of a new algorithmic approach, as we show here. In a fixed confidence setting, we introduce a novel notion of complexity, which accounts for the balance between arm evaluation and (parametric) weight function estimation, establish lower bounds and propose an algorithm proved to be near optimal. Theoretical guarantees are backed up by numerical results.